ECONOMIC ANALYSIS OF 22m AND 23m DEEP SEA TRAWLERS - UNNITHAN, G R; IYER, H KRISHNA; RAO, P SRINIVASA (Fishery Technology, 2017)
The cost-benefit analysis of 23m and 22m trawlers operated from Visakhapatnam base is presented. The study :indicated that the deep sea:fishing in Indian waters is a profitable venture. The profit over capital investment for a 23m trawler worked out to about 18% whereas the same was about 10% for a 22m trawler. Catch per trawling operation, cost of production, productivity per man year, energy yield etc. establish the economic superiority of 23m vessel.